The Educational and Learning Problematic at Senior High School - Santosa, Tomi Apra; Zulyusris, Zulyusri; Suwars, Abi; Amalia, Khodzijah Nur (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2021)
This study aims to determine the problems of education and learning in SMA Negeri 12 Kerinci and SMA Negeri 7 Kerinci. The research used is qualitative research with library research methods. Data collection techniques are observation, interviews, and documentation. The data analysis technique is done by collecting articles, analyzing, and drawing a conclusion. The results of the study concluded that SMA Negeri 12 Kerinci experienced educational and learning problems, namely the lack of science laboratory facilities and infrastructure, the lack of computers for the Computer-Based National Examination (UNBK), and the lack of student activity in the teaching and learning process. SMA Negeri 7 Kerinci is experiencing educational and learning problems, namely the lack of management of school facilities and infrastructure and the lack of learning media in the teaching and learning process.